Incidence of Avascular Necrosis of the Femoral Head After Intramedullary Nailing of Femoral Shaft Fractures: A Multicenter Retrospective Analysis of 542 Cases. Issue 5 (February 2016) - Kim, Ji Wan; Oh, Jong-Keon; Byun, Young-Soo; Shon, Oog-Jin; Park, Jai Hyung; Oh, Hyoung Keun; Shon, Hyun Chul; Park, Ki Chul; Kim, Jung Jae; Lim, Seung-Jae
Abstract : Abstract: The goal of this study was to determine the incidence of avascular necrosis of the femoral head (AVNFH) after intramedullary nailing of femoral shaft fractures and to identify risk factors for developing AVNFH. We retrospectively reviewed all patients with femoral shaft fractures treated with antegrade intramedullary nailing at 10 institutions. Among the 703 patients enrolled, 161 patients were excluded leaving 542 patients in the study. Average age was 42.1 years with average follow-up of 26.3 months. Patient characteristics and fracture patterns as well as entry point of femoral nails were identified and the incidence of AVNFH was investigated. Patients were divided into 2 groups according to open versus closed physis, open versus closed fractures, and age (<20 versus ≥20 years). Overall incidence of AVNFH was 0.2% (1 of 542): the patient was 15-year-old boy. Of 25 patients with open physis, the incidence of AVNFH was 4%, whereas none of 517 patients with closed physis developed AVNFH ( P < 0.001). The incidence of AVNFH in patients aged < 20 versus ≥20 years was 1.1% (1 of 93) and 0.0% (0 of 449), respectively ( P = 0.172), which meant that the incidence of AVNFH was 0% in adult with femur shaft fracture. Of 61 patients with open fractures, the incidence of AVNFH was 0%. The number of cases with entry point at the trochanteric fossa or tip of the greater trochanter (GT) was 324 and 218, respectively, and the incidence of AVNFH was 0.3% and 0.0%, respectively ( P = 0.412). In patients aged ≥20 years with isolated femoral shaft fracture, there was no case of AVNFH following antegrade intramedullary nailing regardless of the entry point. Therefore, our findings suggest that the risk of AVNFH following antegrade femoral nailing is extremely low in adult patients.